(untitled) (Journal of Plant Disease Sciences, 2017)
Chilli ( L.) is Capsicum annuum temperate annual plant commonly cultivated for its vegetable purpose and dry chilli as spice of commerce. It is good source for culinary uses, arthritis pain, diabetic neuropathy and headache. Chilli is a rich source of vitamin C, B, B , carotene 6 (provitamin A), high in potassium (K), magnesium (Mg) and iron (Fe). In India, it is an important cash crop, which is grown for the both domestic and export market. India is the largest producer of chilli occupying about 0.82 million hectare area in the world followed by China (4 lakh tonnes) Raja et al. (2013). Among the biotic stresses, seedling rot of chilli caused by , is Rhizoctonia solani the most serious disease and has national importance as it affects the seedling during the early stages. It causes rot/necrosis of the seedling and rottening of the plants. Chilli is also affected by various fungi . viz Anthracnose ( spp.) Collectotrichum Cercospora leaf spot ( ), Cercospora capsici Bacterial leaf spot (Xanthomonas campestris pv ), viruses TSWV (TSW virus). vesicatoria Among the fungal diseases, damping off disease of seedling as well as root and stem rot in young transplants of chilli caused by Rhizoctonia solani is major soil borne disease causing huge economic losses in chilli. Antagonistic fungi and bacteria; therefore, assumes great significance, among the antagonistic fungi, Trichoderma harzianum has shown promise as a biocontrol agent for R. solani et al Kumar . (2012). A field experiment to test the effect of on severity of Trichoderma seedling rot of chilli (C L.) apsicum annuum caused by on growth and Rhizoctonia solani yield parameters was investigated at our adopted village Banda, district Katni, for suppressing and seedling rot of chilli promoting healthy plant growth and fruit size. The field trial was laid out with 6 treatments